Current limitations and opportunities in mobile augmented reality applications - Nazri, N.I.A.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
Mobile AR has evolved from the bulkiness of head-mounted device and backpack device to smart device (smartphone, tablet etc.). To date, the current implementation has made what AR is today. However, the advancement of AR technology has met with limitation and challenges on its own, which resulted in not able to reach mass-market. This paper in turn presents current limitations and challenges that need to overcome. We have done a review based on past research papers on limitation in technical (hardware, algorithms and interaction technique) and non-technical (social acceptance, privacy and usefulness) aspects of developing and implementing mobile augmented reality applications. We also presented some future opportunities in mobile AR applications. Â© 2014 IEEE.